Pengaruh Kedisiplinan terhadap Hasil Belajar Kelas 3 SD Negeri Buntalan Tahun Ajaran 2023/2024 - Putri Zudhah Ferryka; Sri Suwartini; Heldan Edwin Muhammad Nur (Institut Nalanda, 2024)
This research was motivated by the problem of students who lack discipline when participating in learning at school. The aim of this research is to find out whether the impact of discipline has an influence on student learning outcomes at SD Negeri 3 Buntalan. This type of research is quantitative. The data collection techniques used were interviews, questionnaires and documentation. This research took a sample of 15 students consisting of class III at SD Negeri 3 Buntalan. The analysis technique uses a validity test, a reliability test uses Cronbach's Alpha while the hypothesis test uses a simple linear regression test. The research results obtained have a 62.5% impact on discipline that influences student learning outcomes, while 37.5% comes from other impacts that are not included in the research This. This impact takes the form of a positive impact on student learning outcomes. It has been declared accepted by simple regression calculations.